Magnetic field penetration through a circular aperture in a perfectly conducting plate excited by a coaxial loop. Issue 10 (31st March 2021) - Lovat, Giampiero; Burghignoli, Paolo; Araneo, Rodolfo; Celozzi, Salvatore
Abstract: The transmission of an electromagnetic field produced by a current loop of finite radius through a coaxial circular aperture in a perfectly conducting plate is evaluated through a rapidly convergent formulation in an exact form. By applying the equivalence principle, the problem is first formulated in the Hankel transform domain, obtaining a set of dual integral equations in which the equivalent surface magnetic current density defined on the aperture is not known. The set of dual integral equations is regularised in a second‐kind Fredholm integral equation by applying the Abel integral‐transform technique. The solution is achieved by expanding the unknown in a set of orthogonal basis functions that correctly reproduce the behaviour of the equivalent magnetic current at the edge of the aperture. Finally, under particular assumptions, a low‐frequency solution is extracted in a closed form. Numerical results are reported to validate the accuracy and efficiency of the proposed formulations.